Performance evaluation of alsi10mg mould insert material fabricated by selective laser melting process - Ahmad Raus, Azli Amin (2019)
In this thesis the physical properties, mechanical properties, different profile building feasibility and dimension accuracy of AlSi10Mg samples fabricated by selective laser melting (SLM) technique, as well as novel fabrication strategies as an alternative to conventional methods in order to produce of plastic injection mould (PIM) tools was investigated. Response surface method (RSM) and variance analysis (ANOVA) are utilized to optimize the SLM parameters and develop the mathematical models. The optimum values input parameters for laser power, scan speed and hatch distance recommended to achieve optimum value of relative density and ultimate tensile strength (UTS) were 348.14 Watt, 1483.25 mm/s and 0.1207 mm, respectively. Other than almost full density achievement with the value of 99.3547% from the experiment, the experimental value of UTS (411.881MPa) was higher compared to A360F and A360T6 HDPC alloys. The feasibility and accuracy results indicate that the benchmark model fabricated by SLM technique revealed the potential of producing near net shape parts. Only 0.5mm offset was added in the normal direction during the fabrication of PIM tool inserts for post-processing purpose. The total time reduction in fabricating the PIM tool inserts using the combination of SLM and high speed machining (HSM) strategy was 34 hours. By introducing square fin conformal cooling channel (SFCCC) in PIM tool inserts has shorten the cycle time and improved the injected product quality due to uniform and faster heat dissipation during the moulding cycle. Whereas the total impact of conformal cooling channel and AlSi10Mg as PIM tool insert materials led to almost 32% reduction on cycle time during the moulding cycle compared to the reference PIM tool. Although with the reduction of fabrication time and cycle time, still the cost modelling result highlights that, in order the SLM AlSi10Mg fabricated PIM with square fin conformal cooling to be cheaper than the reference PIM, an endurance of at least 40 000 cycles is required.